Geothermal Heat In Agriculture: Preliminary Results of an Energy Intensive System in Iceland - Dell, Robert (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2011)
A new energy intensive outdoor shallow system of geothermal heated ground agriculture was constructed and has been tested at the Agricultural University of Iceland in Hveragerdi since 2007. The 5 by 10 square meter experimental heated garden and a 5 by 5 square meter control garden both have three different soil mixtures and depths of 10 and 20 centimeters (cm) over a piping system that is analogous to a heated sidewalk. A geothermal borehole supplies steam and steam condensate at temperatures from 100°-125˚C. A traditional shell and tube heat exchanger circulates a mixture of water and automotive anti-freeze continuously throughout the year in a closed loop at temperatures between 45-65˚C. Soil temperatures at 10 cm depth range from 25-40˚C.